Total Polyphenols Content and Antioxidant Activity of Different Tea Commercially Produced in Nepal - Shrestha, Rojeena; Lama, Jiwan Pravan; Shrestha, Kshitij (Journal of Food Science and Technology Nepal, 2013)
This study was conducted to assess and compare the total polyphenol content (TPC), antioxidant activity of different tea varieties commercially produced in Nepal. Nine different brands of tea samples, three from each CTC, orthodox and green tea were collected from different parts of Kathmandu valley. TPC was analyzed as per folin-ciocalteu method and antioxidant activity as per DPPH (2, 2-diphenyl-1-picrylhrdrazine) free radical scavenging capacity. The TPC was found to be 4.60, 8.79, 18.20mg of phenol equivalent (PE)/gm of sample in CTC, orthodox and green tea respectively. Green tea Emerald and green tea Kanchanjunga contained the highest level of polyphenol. Antioxidant activity (for 0.36 mg of tea sample) was found to be 25.04, 43.86, and 72.39% for CTC, orthodox and green tea respectively. Moreover, some commercial brands of green tea (Emerald and Kanchanjunga) showed the highest antioxidant activity. The TPC and antioxidant activity of different commercial brands of tea were found to be positively correlated (r=0.97). J. Food Sci. Technol. Nepal, Vol. 6 (73-77), 2010 DOI: http://dx.doi.org/10.3126/jfstn.v6i0.8264